(NaPPROKSIMACII pADE (B/s - (NbEJKER(B, (NdVORDV ML(B.s; (NgREJWS(B-(NmORRIS(B, (NpITERs; (NrAHMANOW(B, (Ni(B.(Nw(B.s; (NrAHMANOW(B, (Ne(B.(Na(B.s; (NsUETIN(B, (Ns(B.(Nps; (NgON^AR(B, (Na(B.(Na(B.s ((NmOSKWA (B:s (NmIR(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 460-495s
(NpREDM(B. (NUKAZ(B.: (NS(B. 496-499s
Keywords: (NaPPROKSIMACIQ (B((NMAT(B.)s